Seawater carbonate chemistry and gastropod shell dissolution and microstructure - Xing Li; Haijun Song; Li Tian; Xiangmin Chen; Xin Sun; Jia Yan; Enhao Jia; Yan Feng; Daoliang Chu (PANGAEA, 2025)
This study examines the shell growth, surface erosion, and microstructural changes of the marine gastropod Lunella coronata granulata after 85 days of exposure to varying pH (8.1–7.1). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-04-30.